Cardiac energetics, oxygenation, and perfusion during increased workload in patients with type 2 diabetes mellitus - Levelt, E; Rodgers, C; Clarke, W; Mahmod, M; Ariga, R; Francis, J; Liu, A; Wijesurendra, R; Dass, S; Sabharwal, N; Robson, M; Holloway, C; et al. (Oxford University Press, 2015)
Patients with type 2 diabetes mellitus (T2DM) are known to have impaired resting myocardial energetics and impaired myocardial perfusion reserve, even in the absence of obstructive epicardial coronary artery disease (CAD). Whether or not the pre-existing energetic deficit is exacerbated by exercise, and whether the impaired myocardial perfusion causes deoxygenation and further energetic derangement during exercise stress, is uncertain.Thirty-one T2DM patients, on oral antidiabetic therapies with a mean HBA1c of 7.4 ± 1.3%, and 17 matched controls underwent adenosine stress cardiovascular magnetic resonance for assessment of perfusion [myocardial perfusion reserve index (MPRI)] and oxygenation [blood-oxygen level-dependent (BOLD) signal intensity change (SIΔ)]. Cardiac phosphorus-MR spectroscopy was performed at rest and during leg exercise. Significant CAD (>50% coronary stenosis) was excluded in all patients by coronary computed tomographic angiography. Resting phosphocreatine to ATP (PCr/ATP) was reduced by 17% in patients (1.74 ± 0.26, P = 0.001), compared with controls (2.07 ± 0.35); during exercise, there was a further 12% reduction in PCr/ATP (P = 0.005) in T2DM patients, but no change in controls. Myocardial perfusion and oxygenation were decreased in T2DM (MPRI 1.61 ± 0.43 vs. 2.11 ± 0.68 in controls, P = 0.002; BOLD SIΔ 7.3 ± 7.8 vs. 17.1 ± 7.2% in controls, P < 0.001). Exercise PCr/ATP correlated with MPRI (r = 0.50, P = 0.001) and BOLD SIΔ (r = 0.32, P = 0.025), but there were no correlations between rest PCr/ATP and MPRI or BOLD SIΔ.The pre-existing energetic deficit in diabetic cardiomyopathy is exacerbated by exercise; stress PCr/ATP correlates with impaired perfusion and oxygenation. Our findings suggest that, in diabetes, coronary microvascular dysfunction exacerbates derangement of cardiac energetics under conditions of increased workload.